The last giants: New evidence for giant Late Triassic (Rhaetian) ichthyosaurs from the UK. - Dean R Lomax; Paul de la Salle; Marcello Perillo; Justin Reynolds; Ruby Reynolds; James F Waldron (PLoS ONE)
Giant ichthyosaurs with body length estimates exceeding 20 m were present in the latest Triassic of the UK. Here we report on the discovery of a second surangular from the lower jaw of a giant ichthyosaur from Somerset, UK. The new find is comparable in size and morphology to a specimen from Lilstock, Somerset, described in 2018, but it is more complete and better preserved. Both finds are from the uppermost Triassic Westbury Mudstone Formation (Rhaetian), but the new specimen comes from Blue Anchor, approximately 10 km west along the coast from Lilstock. The more complete surangular would have been >2 m long, from an individual with a body length estimated at ~25 m. The identification of two specimens with the same unique morphology and from the same geologic age and geographic location warrants the erection of a new genus and species, Ichthyotitan severnensis gen. et sp. nov. Thin sections of the new specimen revealed the same histological features already observed in similar giant ichthyosaurian specimens. Our data also supports the previous suggestion of an atypical osteogenesis in the lower jaws of giant ichthyosaurs. The geological age and giant size of the specimens suggest shastasaurid affinities, but the material is too incomplete for a definitive referral. Ichthyotitan severnensis gen. et sp. nov., is the first-named giant ichthyosaur from the Rhaetian and probably represents the largest marine reptile formally described.